Hidden skewness - Ludwig Ensthaler; Olga Nottmeyer; Georg Weizsäcker (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We provide laboratory evidence that people neglect skewness resulting from compound shocks.
Keywords: C91; D03; 330; Skewness; belief biases; binomial tree; Verhaltensökonomik; Wahrnehmung; Bias; Statistische Verteilung